Power Engineering 2016
DOI: 10.1201/9781315386829-129
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of wireless MEMS accelerometer for reciprocating compressor condition monitoring

Abstract: With recent development in wireless communication and Micro Electro Mechanical Systems (MEMS) technology, it becomes easier to monitor rotating machinery conditions by mounting compact wireless MEMS accelerometers directly on the rotor. This has the potential to provide more accurate dynamic characteristics of the rotating machine and hence achieving high monitoring performance. In this paper, a tiny MEMS accelerometer together with a battery powered microcontroller is mounted on the flywheel to acquire the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The speed estimation algorithm presented in that study was tested on a rotor operating at a range of speeds between 200 RPM and 2000 RPM and, by comparing the results obtained using the MEMS accelerometer with the speed measured by the encoder, they confirmed that their method was robust and could be applied to rotors irrespective of the state of vibration and during both acceleration and deceleration [11]. As the authors of [7,12] explain, one of the most critical issues in using on-rotor MEMS accelerometers is obtaining the pure tangential acceleration from accelerometer outputs which also contain gravitational acceleration, in order to characterise the rotor dynamics precisely and use them for condition monitoring. In [7], they mounted a three-axial MEMS data logger on the flywheel of a reciprocating compressor to record the onrotor accelerations.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The speed estimation algorithm presented in that study was tested on a rotor operating at a range of speeds between 200 RPM and 2000 RPM and, by comparing the results obtained using the MEMS accelerometer with the speed measured by the encoder, they confirmed that their method was robust and could be applied to rotors irrespective of the state of vibration and during both acceleration and deceleration [11]. As the authors of [7,12] explain, one of the most critical issues in using on-rotor MEMS accelerometers is obtaining the pure tangential acceleration from accelerometer outputs which also contain gravitational acceleration, in order to characterise the rotor dynamics precisely and use them for condition monitoring. In [7], they mounted a three-axial MEMS data logger on the flywheel of a reciprocating compressor to record the onrotor accelerations.…”
Section: Introductionmentioning
confidence: 69%
“…ADXL345 is small, three-axis accelerometer with high resolution (13-bit) with measurement range up to ±16g. It measures the dynamic acceleration resulting from motion as well as the static acceleration of gravity [12]. Therefore, the signals measured using on-rotor MEMS accelerometers contain the required rotor dynamic information as well as the gravitational accelerations, which have to be removed to obtain the rotor dynamics precisely.…”
Section: Gravity Cancellation Using Two Mems Accelerometersmentioning
confidence: 99%